#TITLE_ALTERNATIVE# - HARDIANTI PUTRI NIM : 11614028, UTAMI
Cesarean delivery is a surgical procedure by making incisions through abdominal wall and uterus to deliver the baby. Surgical Site Infection (SSI) is one of the complications that can prolong postoperative length of stay, including in cesarean section patients. Based on several studies, the use of prophylactic antibiotics can reduce the risk of SSI events. There are several risk factors for SSI events, one of which is the incompatibility of surgical prophylactic antibiotics. In 2017, in one hospital of Bandung, there was an SSI incident in patients after cesarean section. The preliminary study shows there are discrepancies in doses and the timing of prophylactic antibiotics with Standard Operating Procedure (SOP) and the latest recommendations from American Society of Health-System Pharmacist (ASHP). Recommended prophylactic antibiotic dose is 2 g which is given within 60 minutes before incision. The study was conducted to analyze the effect of dose and surgical prophylactic antibiotic administration timing on the incidence of SSI in patients undergoing cesarean section, effect of other risk factors, and effect of ILO on postoperative length of stay. Descriptive and analytic observational studies were conducted retrospectively from medical record data in 2017. The samples included in the data analysis were 290 patients with 12 of them experiencing SSI after cesarean section. Based on the results of the bivariate chisquare analysis, dose (p≥0,05) and prophylactic antibiotic administration timing (p≥0,05; OR: 1,53; 95% CI: 0,48-4,86) do not affect the incidence of SSI in patients after cesarean section. Based on logistic regression analysis, obesity as other risk factor significantly affected the incidence of SSI (p<0,05; OR: 3,71; 95% CI: 1,05-12,50). SSI significantly affected the postoperative length of stay (p<0,05).